Comparison of microwave and conventional heating for CO2 desorption from zeolite 13X. (May 2021) - Ellison, Candice; Hoffman, James; Shekhawat, Dushyant
Highlights: Microwave energy was applied to temperature swing CO2 capture using zeolite 13X. Microwave sorbent regeneration is at least 50 % faster than thermal regeneration. Desorption kinetics are mass diffusion limited during microwave regeneration of 13X. Apparent desorption activation energy is reduced using microwaves for regeneration. Proof-of-concept testing demonstrates feasibility of microwave sorbent regeneration. Abstract: This study investigates microwave irradiation as an alternative to conventional heating for temperature swing adsorption processes. The performance of microwave and conventional heating during sorbent regeneration was evaluated by measuring CO2 desorption from zeolite 13X at different temperatures. Experimentally, a fixed bed of zeolite 13X was saturated by a 150 sccm flow of 15 % CO2 at room temperature followed by sorbent regeneration under nitrogen at 55, 100, or 150 °C by applying either microwave irradiation or conventional heating. Microwaves reduced sorbent regeneration times by at least half compared to regeneration by conventional heating. Under conventional regeneration, desorption curves were resolved into two peaks representing physisorbed CO2 (mass diffusion limited) at low temperature and bicoordinated CO2 (thermally limited) with increasing temperature. Under microwave regeneration, only one desorption peak was observed suggesting that CO2 desorption was limited by mass diffusion through the porous zeolite 13X structure, rather than by temperature. Depending on microwave power, apparent activation energy of the microwave-assisted regeneration was 15.8–18.1 kJ/mol, compared to 41.5 kJ/mol for conventional regeneration. The reduction in apparent activation energy is mainly attributed to selective microwave heating of CO2 adsorption sites (Na + sites) resulting in greater steady state temperatures of Na + relative to framework atoms, suggesting greater heating efficiency due to microwaves compared to conventional heat transfer. Due to rapid cycling and efficient heat transfer to CO2 sites on zeolite 13X, microwave regeneration is found to increase adsorption/desorption cycling productivity and potentially reduce the energy penalty of temperature swing capture.